Correlation between Dermatology Life Quality Index and Psoriasis Area and Severity Index in Patients with Psoriasis: A Cross-sectional Global Healthcare Study on Psoriasis - Julia-Tatjana Maul; Lara W. Maul; Johannes A. Didaskalu; Fernando Valenzuela; Ricardo Romiti; Hannah Peterson; Edwin Korouri; Farah Novoa; Hazel H. Oon; Min Zheng; Jashin J. Wu; Jacob P. Thyssen; et al. (Medical Journals Sweden, 2024)
Quality of life impairment in dermatology patients and severity of psoriasis are quantified by the Dermatology Life Quality Index (DLQI) and the Psoriasis Area and Severity Index (PASI), respectively. The aim of this study is to compare the correlation between PASI and DLQI in patients from different geographical areas and to identify predictors of high DLQI across geographical regions. Correlations between PASI and DLQI were evaluated using Spearman's rank correlation tests and quantile regression. The study included 1,158 patients with psoriasis, with a median (interquartile range) PASI and DLQI of 6.0 (3.0-12.0) and 8.0 (4.0-15.0), respectively. Correlations were demonstrated between PASI and DLQI, both overall and stratified by geographical region. Quantile (median) regression yielded coefficients of 0.75 (95% confidence interval (95% CI) 0.62, 0.88) for Switzerland, 0.50 (95% CI 0.42, 0.58) for Latin America, 0.34 (95% CI 0.16, 0.51) for Asia, and 0.31 (95% CI 0.08, 0.53) for the USA. Current age, age at diagnosis, sex, body mass index, and psoriasis arthritis affected DLQI in Latin America, while education had an impact among patients treated in Switzerland. Few countries were included within each continent; hence, more data from different countries are necessary for generalizability. The study showed correlations between PASI and DLQI among patients in all included geographical regions. The patients' characteristics affecting DLQI vary worldwide.